Gamification improves learning: Experience in a training activity of computer programming in higher education - Mellado, Rafael; Cubillos, Claudio (Journal of computer assisted learning, 2024)
Background Effective learning in computer programming courses has been a constant challenge for university teachers and has become a relevant competence for current professionals. The literature on gamification in learning presents mixed results, mainly due to problems in instructional design and inconsistency in gamification. Studies with positive empirical results on computer programming formative activities and showing under what conditions gamification is effective still need to be included. Objectives This study aimed to quantify the effects of gamification techniques in software tools that support computer programming learning applied to data‐structures university students. The study focused on determining whether there are differences in learning when using gamification techniques in online exercising formative activities. The effects of gamification on learning objectives with diverse complexity are studied. Methods The study was conducted on computer engineering university students following a pretest‐intervention‐posttest design. They were divided into control and experimental groups, where both used a bank of exercises in Moodle to support learning. The experimental group considered gamification techniques, including points, leaderboards, and badges. Results and Conclusions Gamification techniques significantly outperformed in learning gains in exercising activities without gamification. Regarding learning complexity, increasing taxonomic complexity did not negatively affect gamification learning effects. Lay Description What is currently known about the subject matter? Gamification has been explored as a strategy to enhance learning motivation in various educational contexts, including computer programming Literature shows mixed quantitative results on learning improvements under gamification. Few studies cover formative exercises, deal with computer programming tasks, or use a LMS like Moodle. Lack of literature exploring the conditions for effective gamification use, and involving learning objective complexity. What does this paper add to the existing body of research? Quantifies the impact of gamification techniques on learning outcomes, specifically focusing on computer‐programming in university. Provides empirical evidence on gamification significantly improving learning gains compared to non‐gamified data‐structures exercises Gamification is effective in tasks of diverse levels of taxonomic complexity, with consistent effectiveness regardless of learning difficulty. Implications of study findings for practitioners Gamification techniques, can be used in higher education to enhance student engagement and learning outcomes in computer programming The gamification information (e.g. points and ranking) do not require an automatic update, can be processed manually and published daily. It is effective to use gamification for learning tasks of medium‐high difficulty in Moodle on computer programming topics. It is key a thoughtful instructional design when applying gamification, ensuring alignment with learning objectives and task complexity.